Emerging roles of long non‐coding RNA in cancer - Sanchez Calle, Anna; Kawamura, Yumi; Yamamoto, Yusuke; Takeshita, Fumitaka; Ochiya, Takahiro (Cancer science, 2018)
Since comprehensive analysis of the mammalian genome revealed that the majority of genomic products are transcribed in long non‐coding RNA (lncRNA), increasing attention has been paid to these transcripts. The applied next‐generation sequencing technologies have provided accumulating evidence of dysregulated lncRNA in cancer. The implication of this finding can be seen in many forms and at multiple levels. With impacts ranging from integrating chromatin remodeling complexes to regulating transcription and post‐transcriptional processes, aberrant expression of lncRNA may have repercussions in cell proliferation, tumor progression or metastasis. lncRNA may act as enhancers, scaffolds or decoys by physically interacting with other RNA species or proteins, resulting in a direct impact on cell signaling cascades. Even though their functional classification is well‐established in the context of cancer, clearer characterization in terms of their phenotypic outputs is needed to optimize and identify suitable candidates that enable the development of new therapeutic strategies and the design of novel diagnostic approaches. The present article aims to outline different cancer‐associated lncRNA according to their contribution to tumor suppression or tumor promotion based on their most current functional annotations. lncRNAs involved in tumor plasticity. Aberrantly expressed lncRNAs may have an important impact in the EMT‐MET processes by interacting with diverse signaling cascades.